The Influence of Work Stress and Workload on Employee Performance at Bank Bri Begkulu Selatan - Winda NurZuli AyuSari; Sulisti Afriani; Abdul Rahman (UNIVED Press, 2023)
The purpose of this study was to determine the effect of work stress and workload on employee performance at Bank BRI South Bengkulu.The sample in this study was taken as many as 80 employees using the snsus method. This research is a quantitative research using non-probability techniques with purpose sampling method. The instrument in this study was a questionnaire which was then processed using the SPSS version 22.0 computer application. The analytical method used is multiple linear regression analysis and hypothesis testing.The results showed that the results of the regression analysis obtained the equation Y = 19.451+0.443X1+0.510X2+4.981. This illustrates that the product quality variable has the opposite or negative regression direction, meaning that if work stress increases it will actually reduce employee performance. This is because if uncontrolled work stress can make employees lose focus and can cause employee performance to decrease. The workload variable has the same regression direction, which is negative, which means that if the workload variable increases, employee performance will also decrease.The coefficient of determination is 0.272, which means that work stress and workload affect employee performance by 27.2%, while the remaining 72.8% is influenced by other variables not examined in this study.The results of the t test at a significance level of 0.05 explain that partially the work stress and workload variables have a significant influence on employee performance variables because the significance value is <0.05.The results of the F test at a significance level of 0.05 explain that the variables Work Stress, Workload have a simultaneous (together) influence on purchasing decisions because the Significance Value is <0.05.